Human bocavirus, coronavirus, and polyomavirus detected among patients hospitalised with severe acute respiratory illness in South Africa, 2012 to 2013. Issue 8 (18th July 2018) - Subramoney, Kathleen; Hellferscee, Orienka; Pretorius, Marthi; Tempia, Stefano; McMorrow, Meredith; von Gottberg, Anne; Wolter, Nicole; Variava, Ebrahim; Dawood, Halima; Kahn, Kathleen; Walaza, Sibongile; Madhi, Shabir A.; et al.
Abstract: Aim: To investigate the prevalence of human bocavirus (hBoV), human coronaviruses (hCoV), and human polyomaviruses (hPyV) among patients with severe acute respiratory illness (SARI), in South Africa. Methods: The study included 680 South African patients randomly selected in age‐defined categories from hospitalised patients enrolled through SARI surveillance during 2012 to 2013. A multiplex reverse transcription real‐time polymerase chain reaction assay was used to detect hBoV; hCoV‐OC43, hCoV‐229E, hCoV‐NL63, and hCoV‐HKU1; and Washington University hPyV (hPyV‐WU) and Karolinska Insitute hPyV (hPyV‐KI), in respiratory tract specimens collected from patients with SARI. All respiratory specimens from patients enrolled through SARI surveillance were also routinely tested by multiplex reverse transcription real‐time polymerase chain reaction for adenovirus; enterovirus; human metapneumovirus; parainfluenza virus types 1, 2, and 3; respiratory syncytial virus; rhinovirus; influenza A, and influenza B. Results: Human bocavirus, hCoV‐229E, and hPyV‐WU were detected in 3.7% (25/680), 4.1% (28/680), and 4.1% (28/680) of respiratory specimens, respectively. All other viruses were detected in <2% of specimens. Rhinovirus was the most common coinfecting virus (21.4%‐60.7%), followed by adenovirus (21.4%‐39.3%), and respiratory syncytial virus (10.7%‐24.0%). Testing for the additional viruses (hBoV, hCoV, and hPyV) decreased the number of specimens that initially tested negative by 2.9% (20/680). Conclusion: Inclusion of laboratory tests for hBoV, hCoV‐229E, and hPyV‐WU in differential testing algorithms for surveillance and diagnostics for suspected cases of respiratory illness of unknown cause may improve our understanding of the etiology of SARI, especially in a country like South Africa with a high number of immune compromised persons. Abstract : Aim To investigate the prevalence of human bocavirus (hBoV), human coronaviruses (hCoV), and human polyomaviruses (hPyV) among patients with severe acute respiratory illness (SARI), in South Africa. Methods The study included 680 South African patients randomly selected in age‐defined categories from hospitalised patients enrolled through SARI surveillance during 2012 to 2013. A multiplex reverse transcription real‐time polymerase chain reaction assay was used to detect hBoV; hCoV‐OC43, hCoV‐229E, hCoV‐NL63, and hCoV‐HKU1; and Washington University hPyV (hPyV‐WU) and Karolinska Insitute hPyV (hPyV‐KI), in respiratory tract specimens collected from patients with SARI. All respiratory specimens from patients enrolled through SARI surveillance were also routinely tested by multiplex reverse transcription real‐time polymerase chain reaction for adenovirus; enterovirus; human metapneumovirus; parainfluenza virus types 1, 2, and 3; respiratory syncytial virus; rhinovirus; influenza A, and influenza B. Results Human bocavirus, hCoV‐229E, and hPyV‐WU were detected in 3.7% (25/680), 4.1% (28/680), and 4.1% (28/680) of respiratory specimens, respectively. All other viruses were detected in <2% of specimens. Rhinovirus was the most common coinfecting virus (21.4%‐60.7%), followed by adenovirus (21.4%‐39.3%), and respiratory syncytial virus (10.7%‐24.0%). Testing for the additional viruses (hBoV, hCoV, and hPyV) decreased the number of specimens that initially tested negative by 2.9% (20/680). Conclusion Inclusion of laboratory tests for hBoV, hCoV‐229E, and hPyV‐WU in differential testing algorithms for surveillance and diagnostics for suspected cases of respiratory illness of unknown cause may improve our understanding of the etiology of SARI, especially in a country like South Africa with a high number of immune compromised persons.